Perangkat Lunak Open Source dan Arkeologi - Andri Restiyadi (Berkala Arkeologi Sangkhakala, 2011)
AbstractComputers were created to facilitate and accelerate the work of man. Archaeology as a discipline that is struggling with the database and the document will certainly take advantage of this technology. Many data are currently processed using a computer. However, software prices are still expensive, thus make some crucial software being pirated to make it functional and can be used. Open source software has been emerged as an attractive alternative for used as needed. Through explorative-descriptive method, in this case will be presented of the use of open source softwarefor archaeology.